Influence of living green fertilizers on soil fertility and growth of Tectona grandis in the Santo Domingo, Ecuador - Jiménez-Pozo, Lenin Patricio (2025)
The purpose of this research was to evaluate the influence of three green fertilizers compared to  a control, regarding soil fertility and the initial growth of a Teca plantation. This research was carried out in Santo Domingo of the Tsáchilas, Ecuador, during the period June 2018 to June 2019, working with three green fertilizers (A. pintoi, P. vulgaris and C. pubescens) and a control (weeds): The variables evaluated were: (a) the soil nutritional content (pH, OM content, macronutrients and micronutrients), (b) plant height, (c) plant diameter and (d) biomass.,. The results showed no differences in the nutritional content of the soil, ans that the use of any of the green fertilizer improves plant height. There was a direct relationship between the height of the plant and its diameter, which was evident from day 120 of evaluation. Finally, when evaluating the influence of green fertilizers on biomass, it was confirmed that they have a high capacity to control the incidence of weeds. Therefore, the use of green fertilizers favors the development of the plant without harming the environment.